A study of Kapandji intrafocal pinning for the treatment of unstable extra articular distal radius fractures - Khadka, Titjhendra; Marasini, Rudra Prasad; KC, Dirgha Raj; Tamrakar, Rojan; Thapa, Prakash Bahadur; Kharel, Yagyar Raj; Shah, Gyanendra; Poudel, Krishna Prasad (Journal of Chitwan Medical College, 2017)
Intrafocal pinning of distal radius fracture is indicated in unstable distal radius fractures without significant intra-articular displacement. It is a simple and effective, minimally invasive method of fixation for achievement of alignment and stability of unstable fractures. The study was conducted between November 2013 and October 2016. Patients attending the emergency and outpatient departments with history of trauma followed by pain and swelling of wrist, were evaluated clinically & radiologically. Patients with distal radius fracture who met the criteria were enrolled in the study. The operation was performed either under regional anaesthesia or intra venous anaesthesia. Reduction was carried out under image intensifier guidance and intrafocal pinning was undertaken with 2 Kirschner wires as described by Kapandji. Above elbow slab was applied for 3 weeks. Kirschner wires were removed at 6th week. Follow ups were done with radiological and functional evaluation on 1st week, 3rd week, 6th week, 12th week and 6 month. Of the 30 cases enrolled in our study, the age ranged from 40 to 72 years and the mean age of the patients was 54.77 years. The female/male ratio was 5:1 and the majority (83%) of patient sustained injury due to trivial trauma. All fractures united by 6 weeks. In the final follow up at 6th month, assessment of range of motion showed almost full range of motion. Functional evaluation was carried out with Gartland & Werleys Demerit point system (modified by Sarmiento et al). According to the score, 9 patients had excellent, 19 had well and 2 had fair results. None of the patient had poor results. Kapandji intrafocal pinning provides a stable fixation and good functional outcome in extraarticular distal radius fractures with few complications only.